Mechanical properties of clayey soil relevant for clogging potential - Alberto-Hernandez, Yolanda (2017)
Due to its advantages, including reduced operation time and cost, tunnelling with boring machines in urban areas has become a popular technique over hand-tunnelling or open-trench excavations. However, tunnelling in clayey soil poses a great challenge since the mechanical and physical properties of clays cause different issues, one of which is clogging. To solve this problem, engineers have treated the soils with different soil conditioners in order to change their rheological properties, improve their manageability and eliminate undesirable characteristics. However, the root of this problem is the lack of understanding the phenomenon and characterising it on the framework of soil mechanics. By considering the use of polymers, this paper aims to provide information regarding the theory involved in this mechanism and the factors influencing clogging potential. The authors present a systematic study of the physical and mechanical properties of plain soil and conditioned soil, which includes a direct shear test, vane shear test and Atterberg limits test. Results show that the initial water content, roughness of shear plate and percentage of additive have a significant effect on the clogging potential. Additionally, the results are plotted on an empirical diagram to understand the clogging potential by relating the clogging potential to soil properties.